Serum Phosphorus Levels, Race, and Socioeconomic Status in Incident Hemodialysis Patients - Kumar, Victoria A; Tilluckdharry, Natasha; Xue, Hui; Sidell, Margo A (Journal of renal nutrition, 2016)
We sought to examine the relationship between race, socioeconomic status, and serum phosphorus levels in patients with end-stage renal disease incident to hemodialysis (HD) at a large, integrated health-care delivery system in Southern California. Retrospective cohort study. A total of 5,778 adult patients who initiated HD at our institution between January 1, 2007 and June 30, 2013. Unadjusted and adjusted time-averaged serum phosphorus levels and actual phosphorus levels over time. Phosphorus levels were also analyzed by repeated measures as a continuous measure and by phosphorus category. Baseline patient covariates included age, self-reported race, gender, cause of end-stage renal disease, and Charlson comorbidity index scores. Education and income level were estimated using geocoded data. A total of 68,372 phosphorus levels were available for 4,862 patients. Estimated annual family income fell below $40,001 in 66.1% of African Americans (AAs) and 62.7% of Hispanics compared with 43.5% of Asians and 43.7% of whites, P < .0001. Educational level fell into the highest category for whites (70.8%) compared with AA (44.8%) or Hispanic (30.5%) patients, P < .0001. Adjusted time-averaged phosphorus levels were lower among Hispanics (4.33 mg/dL, 95% confidence interval [CI] 4.27-4.40) compared with Asian (4.54 mg/dL, 95% CI 4.45-4.64, P < .001) and white patients (4.48 mg/dL, 95% CI 4.43-4.54, P < .001) but similar to AA patients. Asian patients experienced a significant increase in phosphorus levels over time (0.11 mg/dL per year, P < .0001). There were no significant effects of race, time, or race by time interactions in the unadjusted and adjusted categorical analyses of phosphorus levels. Our findings suggest that serum phosphorus levels are similar among HD patients, irrespective of race or socioeconomic status.